SPEAKING SKILL CONTRIBUTIONS ON STUDENTS OF USU FUTURE CAREERS - Muhammad Aqil An Nabil; Yulianus Harefa; Mohammad Syafi'ie Siregar (BAHAS, 2021)
Abstract   This research dealt with the common phenomena in the contributions of speaking skill on students’ future careers. The objectives of this study were: (1) to find out students of English Department perceptions about the contribution of speaking skills to their career; (2) to find out the effects of the contribution of speaking skill to students of English Department career performance. The data were obtained from the utterances of thirty graduates English department students of University of North Sumatra that has involved in the professional world. The research applied qualitative research design. The data were collected through collecting the questionnaire. The findings of this study showed that: (1) all participants had a positive perception on the contribution of speaking skill to their career; (2) Speaking skill could enhance students’ communication and interaction, speaking skill support in conducting a successful interview, speaking skill help students in doing job interview, by being able expressing themselves. Keyword: Speaking skill, Students, Contributions, Career